The role of deliberate practice in expert performance: revisiting Ericsson, Krampe & Tesch-Römer (1993) - Macnamara, B. N.; Maitra, M. (Royal Society Open Science, 2019)
We sought to replicate Ericsson, Krampe & Tesch-Römer`s (Ericsson, Krampe & Tesch-Römer 1993 Psychol. Rev. 100, 363-406) seminal study on deliberate practice. Ericsson et al. found that differences in retrospective estimates of accumulated amounts of deliberate practice corresponded to each skill level of student violinists. They concluded, `individual differences in ultimate performance can largely be accounted for by differential amounts of past and current levels of practice` (p. 392). We reproduced the methodology with notable exceptions, namely (i) employing a double-blind procedure, (ii) conducting analyses better suited to the study design, and (iii) testing previously unanswered questions about teacher-designed practice—that is, we examined the way Ericsson et al. operationalized deliberate practice (practice alone), and their theoretical but previously unmeasured definition of deliberate practice (teacherdesigned practice), and compared them. We did not replicate the core finding that accumulated amounts of deliberate practice corresponded to each skill level. Overall, the size of the effect was substantial, but considerably smaller than the original study`s effect size. Teacher-designed practice was perceived as less relevant to improving performance on the violin than practice alone. Further, amount of teacherdesigned practice did not account for more variance in performance than amount of practice alone. Implications for the deliberate practice theory are discussed.